2023
DOI: 10.1038/s41598-023-28521-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and local adaption of alfalfa populations (Medicago sativa L.) under long-term grazing

Abstract: Genomic information on alfalfa adaptation to long-term grazing is useful for alfalfa genetic improvement. In this study, 14 alfalfa populations were collected from long-term grazing sites (> 25 years) across four soil zones in western Canada. Alfalfa cultivars released between 1926 and 1980 were used to compare degree of genetic variation of the 14 populations. Six agro-morphological and three nutritive value traits were evaluated from 2018 to 2020. The genotyping-by-sequencing (GBS) data of the alfalfa pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Our previous study found that the 141 genotypes representing 14 alfalfa populations from long‐term grazing were hybrid between the subspecies of M. sativa and M. falcata with a similar population structure (Wang et al., 2023). In this study, we also found that the genomic relationship among these 141 genotypes was close as indicated by GRM values ranging from −0.1 to 0.6, further confirming a similar genetic structure found in our previous study (Wang et al., 2023). This might contribute to a relatively higher prediction accuracy when using training populations over 1000 repeats in our study, as closely related populations usually had higher GS prediction accuracy compared to unrelated or distantly related populations (Habier et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study found that the 141 genotypes representing 14 alfalfa populations from long‐term grazing were hybrid between the subspecies of M. sativa and M. falcata with a similar population structure (Wang et al., 2023). In this study, we also found that the genomic relationship among these 141 genotypes was close as indicated by GRM values ranging from −0.1 to 0.6, further confirming a similar genetic structure found in our previous study (Wang et al., 2023). This might contribute to a relatively higher prediction accuracy when using training populations over 1000 repeats in our study, as closely related populations usually had higher GS prediction accuracy compared to unrelated or distantly related populations (Habier et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The details on plant materials, experimental design, phenotypic data collection, DNA extraction, and sequencing are described in Wang et al. (2023). In brief, 14 alfalfa populations were collected from 14 grazing sites with a minimum of 25 years of use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, NDF is the most common measure of fiber used for animal feed analysis but does not represent a unique class of chemical compounds. NDF measures most of the structural components of plant cells such as cellulose, hemicellulose, and lignin but not pectin [71]. In general, both ADF and NDF values increased as the forage matured.…”
Section: Treatment Combination and Genotypes Selection Using The Mgidimentioning
confidence: 98%